The essence of gypsum's influence on Tmax of source rocks: a case study of the Lower Ganchaigou Formation of Paleogene in western Qaidam Basin - Wen QI; Feng CHEN; Peng FANG; Bin ZHANG; Shuo GAO; Zhibin HONG; Ping ZHANG; Jia WU (Shiyou shiyan dizhi, 2023)
Geological observation and thermal simulation experiments have revealed that the peak period of hydrocarbon generation of gypsum-bearing mudstone is often advanced in sedimentary basins, but the correlation between the amount of advance and the content of gypsum is still not clear. In this study, the source rock powder samples with different gypsum content in the Lower Ganchaigou Formation from well S49-1 in the western Qaidam Basin were selected and extracted to remove soluble organic matter (SOM). Part of the extracted residue was pickled to remove carbonate. Rock pyrolysis analysis was performed on the original samples and the solid residue after two-step pretreatment. Compared to the Tmax of original samples, the Tmax was higher in the SOM-free residue but lower in the SOM-free and carbonate-free residue, showing that SOM and sulfate minerals (gypsum and anhydrite) in gypsum-bearing mudstone can promote the thermal evolution of organic matter. Although the latter has a more significant effect, it is not proportional to its sulfate content, indicating that the contact area of sulfate minerals and organic matter is more important to Tmax. The hypothesis was verified by the Tmax values of different proportions of kerogen and magnesium sulfate powder mixtures. Therefore, the occurrence state of sulfate minerals will directly affect the contact relationship between organic matter and sulfate, which in turn will affect the process of hydrocarbon generation in thermal evolution.